2011
DOI: 10.1096/fj.11-191429
|View full text |Cite
|
Sign up to set email alerts
|

Effective detection of fetal sex using circulating fetal DNA in first‐trimester maternal plasma

Abstract: The aim of this study was to develop a simple and effective method for noninvasively detecting fetal sex using circulating fetal DNA from first-trimester maternal plasma. A study was conducted with maternal plasma collected from 203 women between 5 and 12 wk of gestation. The presence of circulating fetal DNA was confirmed by a quantitative methylation-specific polymerase chain reaction of the unmethylated-PDE9A gene (U-PDE9A). Multiplex real-time PCR was used to simultaneously quantify the amount of DYS14 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Typically, early sex determination is completed using invasive techniques, such as chorionic villus sampling [7]. These invasive procedures carry an increased risk of miscarriage for the expectant mother [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Typically, early sex determination is completed using invasive techniques, such as chorionic villus sampling [7]. These invasive procedures carry an increased risk of miscarriage for the expectant mother [8].…”
Section: Introductionmentioning
confidence: 99%
“…Results from previous experiments have shown the possibility of fetal DNA in maternal plasma DNA for sex determination [10]. Sex determination is the most common clinical application in NIPT using cfDNA [7]. Different types Y-chromosome specific sequences have been used in previous studies, which vary in specificity and sensitivity [11].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This epigenetic strategy has led to the identification of DNA sequences which are methylated differently in maternal blood and placenta. Chim et al and Lim et al reported that the region of human PDE9A gene, located on chromosome 21q22.3, is completely methylated in the maternal blood ( M-PED9A ) and unmethylated in fetal (placental) tissues ( U-PED9A ) [20][22]. In previous studies, CpG sequences of U-PDE9A were modified by bisulfite conversion and selectively amplified by quantitative methylation-specific PCR (qMSP) [21], [22].…”
Section: Introductionmentioning
confidence: 99%